Secondary analysis of economic data: a review of cost-benefit studies of neonatal screening for phenylketonuria. Issue 3 (1st March 1999) - Lord, J; Thomason, M J; Littlejohns, P; Chalmers, R A; Bain, M D; Addison, G M; Wilcox, A H; Seymour, C A
Abstract : STUDY OBJECTIVE: To estimate the net financial benefit of neonatal screening for phenylketonuria (PKU): by a simple pooling of cost data from the literature; and by a more complex modelling approach. DESIGN: A systematic literature review was conducted to identify papers containing data on the monetary costs and benefits of neonatal screening for PKU. The methodological quality of the studies was appraised, and data were extracted on resource use and expenditure. Monetary data were converted to common currency units, and standardised to UK incidence rates. Net benefits were calculated for median, best case and worst case scenarios, and the effect of excluding poor quality studies and data was tested. The net benefit was also estimated from a model based on data from the literature and assumptions appropriate for the current UK situation. Extensive sensitivity analysis was conducted. MAIN RESULTS: The direct net benefit of screening based on the median costs and benefits from the 13 studies identified was 143, 400 Pounds per case detected and treated (39, 000 Pounds and 241, 800 Pounds for worst case and best case scenarios respectively). The direct net benefit obtained by the modelling approach was lower at 93, 400 Pounds per case detected and treated. Screening remained cost saving under sensitivity analysis, except with low residential care costs (less than 12, 300 Pounds per annum), or very low incidence rates (less than 1 in 27, 000). CONCLUSIONS: The economic literature on PKU screening is of variable quality. The two methods of secondary analysis lead to the same conclusion: that neonatal PKU screening is worthwhile in financial terms alone in the UK, and that it justifies the infrastructure for collecting and testing neonatal blood samples. This result cannot necessarily be extrapolated to other countries.